2020
DOI: 10.1111/dme.14344
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of anxiety symptom trajectories in type 2 diabetes: the Fremantle Diabetes Study Phase II

Abstract: Aim To identify determinants and outcomes of 4‐year trajectories of anxiety symptoms in a community‐based cohort with type 2 diabetes. Methods Some 1091 participants in the Fremantle Diabetes Study‐Phase II with type 2 diabetes completed the Generalized Anxiety Disorder Scale at baseline and biennially for 4 years, in addition to psychological, biomedical and self‐management measures. Latent growth mixture modelling identified trajectories of anxiety symptom severity, and regression models determined predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“… 2-To identify predictors and associates of these trajectories. Psychological science Prevalent cases (n = 1,201) Predictors of trajectories: Clinical, biochemical, demographic, depression, psychosocial data Trajectories of depression symptoms Tool : Patient Health Questionnaire Comparison between groups: One-Way ANOVA, X 2 , Mann-Whitney U test, Kruskal-Wallis test Predictive model: Binary logistic regression model Time-point studied: 2 years Trajectory identification follow-up : 4 years Total follow-up: 4 years Latent class growth analysis [ 30 ] Whitworth 2020 [ 13 ] Cohort: Fremantle Diabetes Study Phase II (2008–2011, follow-up until 2016) Type of data source: Primary data (prospective cohort) 1-To identify distinct trajectories of anxiety symptoms in individuals with T2D over time. 2-To identify demographic, self-management and clinical predictors of anxiety trajectory membership.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2-To identify predictors and associates of these trajectories. Psychological science Prevalent cases (n = 1,201) Predictors of trajectories: Clinical, biochemical, demographic, depression, psychosocial data Trajectories of depression symptoms Tool : Patient Health Questionnaire Comparison between groups: One-Way ANOVA, X 2 , Mann-Whitney U test, Kruskal-Wallis test Predictive model: Binary logistic regression model Time-point studied: 2 years Trajectory identification follow-up : 4 years Total follow-up: 4 years Latent class growth analysis [ 30 ] Whitworth 2020 [ 13 ] Cohort: Fremantle Diabetes Study Phase II (2008–2011, follow-up until 2016) Type of data source: Primary data (prospective cohort) 1-To identify distinct trajectories of anxiety symptoms in individuals with T2D over time. 2-To identify demographic, self-management and clinical predictors of anxiety trajectory membership.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6 studies considered within-class heterogeneity by using LGMM [ 12 , 13 , 14 , 15 , 16 ] or a General Growth Class Mixture Modeling (GGCMM) for randomized intervention [ 17 , 18 ]. Most studies (n = 32) used LCGA.…”
Section: Resultsmentioning
confidence: 99%
“…12,32 In a study with 77 diabetic patients, Balhara et al 33 showed that BMI significantly correlated with anxiety and depression scores. Whitworth et al 34 also stated that high BMI could be a risk factor for anxiety in diabetic patients. Additionally, increased waist circumference was associated with anxiety by Mattei et al, 35 while Labad et al 36 associated it with depression.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression was discovered to be higher in patients with severe glaucomatous disease, and anxiety disorders of glaucoma patients may also increase due to fear of potential blindness and limitation of daily activities ( 32 , 42 ). Diabetes was also reported a risk factor for anxiety disorders ( 43 , 44 ). A meta-analysis provides evidence that diabetes is related to an increased risk of presence of anxiety disorders and elevated anxious symptoms ( 44 ).…”
Section: Discussionmentioning
confidence: 99%